Table of contents, editorial board, and other front matter - Hal A. Taylor (Journal of Applied Communications, 1983)
Editorial front matter and table of contents for vol.66, no.3, July-Sept (1983) of The ACE Quarterly, Official Journal of the Agricultural Communicators in Education